Renal Doppler Resistive Index as a Marker of Oxygen Supply and Demand Mismatch in Postoperative Cardiac Surgery Patients. (29th October 2015) - Corradi, Francesco; Brusasco, Claudia; Paparo, Francesco; Manca, Tullio; Santori, Gregorio; Benassi, Filippo; Molardi, Alberto; Gallingani, Alan; Ramelli, Andrea; Gherli, Tiziano; Vezzani, Antonella
Abstract : Background and Objective . Renal Doppler resistive index (RDRI) is a noninvasive index considered to reflect renal vascular perfusion. The aim of this study was to identify the independent hemodynamic determinants of RDRI in mechanically ventilated patients after cardiac surgery. Methods . RDRI was determined in 61 patients by color and pulse Doppler ultrasonography of the interlobar renal arteries. Intermittent thermodilution cardiac output measurements were obtained and blood samples taken from the tip of pulmonary artery catheter to measure hemodynamics and mixed venous oxygen saturation (SvO2 ). Results . By univariate analysis, RDRI was significantly correlated with SvO2, oxygen extraction ratio, left ventricular stroke work index, and cardiac index, but not heart rate, central venous pressure, mean artery pressure, pulmonary capillary wedge pressure, systemic vascular resistance index, oxygen delivery index, oxygen consumption index, arterial lactate concentration, and age. However, by multivariate analysis RDRI was significantly correlated with SvO2 only. Conclusions . The present data suggests that, in mechanically ventilated patients after cardiac surgery, RDRI increases proportionally to the decrease in SvO2, thus reflecting an early vascular response to tissue hypoxia.